The impact of domestic macroeconomic factors on Chinese cross-border mergers and acquisitions - Deng, Changyong (2017)
With the rapid and sustainable development of China's economy over the past three decades, China’s outward foreign direct investment (FDI) has continuously increased. According to National Bureau of Statistic of China (NBSC, 2015), China’s outward FDI has exceeded inward FDI for the first time in 2014. In this process, a large number of Chinese outstanding enterprises are blooming. After gaining competiveness, some enterprises began to venture abroad to search for new sources of growth. Now Chinese multinational enterprises (CMNEs) have been one of the most significant sources of outward FDI in the world. billion from 2004 to 2015, accounting for 43.6 percent of the total value of outward FDI (Ge, 2016). Among them, the figure is 49.13 percent and 37.3 percent in 2014 and 2015 respectively. Just considering the number of oversea M&A transactions and the scale of such activities, Chinese outward M&As have entered the golden age.